Marketing Strategy Analysis at the Pukik Cangkang Shop in Natar, South Lampung in Surviving Amidst the Covid-19 Pandemic - Septiantini, Septiantini; Gultom, Indriati Agustina (LPPPIPublishing, 2025)
This study aims to determine the appropriate marketing strategy to increase sales of Pukik Cangkang products amidst increasing market competition. The informants in this study were Pukik Cangkang consumers with a minimum age range of 20 years and above. The analytical methods used were IFAS, EFAS, and SWOT analysis to identify the company's internal and external factors. Based on the research results, a SWOT matrix diagram was obtained which showed that Pukik Cangkang's position was in Quadrant I, which is a very favorable situation. This condition illustrates that the company has strengths and opportunities that can be optimally utilized. Therefore, the strategy that should be implemented is an aggressive growth strategy (growth-oriented strategy), by supporting policies that encourage rapid market expansion to expand market share and strengthen the business position amidst industrial competition.